A C-Terminally Truncated TDP-43 Splice Isoform Exhibits Neuronal Specific Cytoplasmic Aggregation and Contributes to TDP-43 Pathology in ALS - Marc Shenouda; Marc Shenouda; Shangxi Xiao; Laura MacNair; Laura MacNair; Agnes Lau; Janice Robertson; Janice Robertson (Frontiers in Neuroscience, 2022)
Neuronal cytoplasmic aggregation and ubiquitination of TDP-43 is the most common disease pathology linking Amyotrophic Lateral Sclerosis (ALS) and frontotemporal lobar degeneration (FTLD). TDP-43 pathology is characterized by the presence of low molecular weight TDP-43 species generated through proteolytic cleavage and/or abnormal RNA processing events. In addition to N-terminally truncated TDP-43 species, it has become evident that C-terminally truncated variants generated through alternative splicing in exon 6 also contribute to the pathophysiology of ALS/FTLD. Three such variants are listed in UCSD genome browser each sharing the same C-terminal unique sequence of 18 amino acids which has been shown to contain a putative nuclear export sequence. Here we have identified an additional C-terminally truncated variant of TDP-43 in human spinal cord tissue. This variant, called TDP43C-spl, is generated through use of non-canonical splice sites in exon 6, skipping 1,020 bp and encoding a 272 aa protein lacking the C-terminus with the first 256 aa identical to full-length TDP-43 and the same 18 amino acid C-terminal unique sequence. Ectopic expression studies in cells revealed that TDP43C-spl was localized to the nucleus in astrocytic and microglial cell lines but formed cytoplasmic ubiquitinated aggregates in neuronal cell lines. An antibody raised to the unique 18 amino acid sequence showed elevated levels of C-terminally truncated variants in ALS spinal cord tissues, and co-labeled TDP-43 pathology in disease affected spinal motor neurons. The retention of this 18 amino acid sequence among several C-terminally truncated TDP-43 variants suggests important functional relevance. Our studies of TDP43C-spl suggest this may be related to the selective vulnerability of neurons to TDP-43 pathology and cell-subtype differences in nuclear export.